Imaging the impurity distribution in glacier ice cores with LA-ICP-MS - Marco Roman; Martin Šala; Carlo Barbante; Pascal Bohleber (Journal of Analytical Atomic Spectrometry, 2020)
The novel combination of ice core LA-ICP-MS with improved imaging techniques reveals impurity localization without artifacts.